(NkOBZAR (B/s - (N{EW^ENKO(B, (NtARAS gRIGOROWI^(B,s; (NmOW^ANA(B, (Np(B.,s; (NnAHL)QÆKA(B, ã.,s)E; (NgARBUZ(B, (Nw(B.s ((NkI)QÇW (B:s)E (NpROSW)QÆTA(B,s)E, 2004)
(NdO KNIGI POETI^NIH TWOR)QÆW GENÆALXNOGO UKRAÇNSXKOGO POETA t(B. (Ng(B. (N{EW^ENKA (B(1814 - 1861) (NUWÆJ[LI WÆR[Æ(B, (NPOEMI(B, (NBALADI(B, (NNAPISANÆ W (B1837 - 1861 (NRR(B.s)E
(NpRIM(B.: (NS(B. 656-679.- (NaLF(B. (NPOKAV^(B.: (NS(B. 684-687s
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NhUDOVNQ L)QÆTERATURAs)E -- (NUKRA)QÇNSXKA LÆTERATURAs)E -- (NPOEZ)QÆÇs)E -- 19 (NST(B.s